2017
DOI: 10.1186/s12889-017-4017-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of breakfast on short-term cognitive function among Chinese white-collar workers: protocol for a three-phase crossover study

Abstract: BackgroundAs the first meal of the day, breakfast plays an important role in supplying energy and nutrients, which are critical to working and learning activities. A three-phase crossover study was designed to investigate the effects of breakfast on cognitive function among Chinese white-collar workers. The planned study protocol is presented.MethodsA total of 264 participants aged 25–45 years will be recruited from Shenyang and Chongqing. Self-administered questionnaires will be used to collect information on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
(24 reference statements)
0
8
0
1
Order By: Relevance
“…For example: A follows B in “AB” (false), B is not preceded by A in “BA” (true). The number of already-completed correct number is measured for score [ 34 ]. (Correct rate (%) = right numbers (n)/already-completed numbers (n) × 100%).…”
Section: Methods and Analysismentioning
confidence: 99%
“…For example: A follows B in “AB” (false), B is not preceded by A in “BA” (true). The number of already-completed correct number is measured for score [ 34 ]. (Correct rate (%) = right numbers (n)/already-completed numbers (n) × 100%).…”
Section: Methods and Analysismentioning
confidence: 99%
“…iAUC data revealed that the increase in postprandial attention was significantly higher after MD than after WD, which is in accordance with our hypothesis that a MD results in higher postprandial attention than a WD. Considering the fact that glucose is the main fuel for brain function and therefore plays an important role in general cognitive performance [29,30], the observed meal effect on postprandial attention in the present study might be due to the higher amount of carbohydrate in MD (133.3 g vs. 93.7 g). It remains unclear whether the different nutrient composition of the breakfast challenges (Table 1) contributed to the observed results.…”
Section: Discussionmentioning
confidence: 70%
“…However, longitudinal observational studies have found that women who consume breakfast everyday were less likely to become obese those women who did not [31] and eating breakfast at home has been associated with the prevention of weight regaining after dieting [32]. Furthermore, consuming breakfast has also been correlated with higher levels of cognitive functioning and academic achievement in adolescents [33, 34]. Therefore, not eating breakfast everyday may not be a favorable health behavior in terms of cognitive functioning or for performance in academic classes but yet may yield negative energy balances for weight loss.…”
Section: Discussionmentioning
confidence: 99%